Development of a Micro-sized Herbal-Based Scalp Oil Serum with Antioxidant and Anti-Inflammatory Properties - HAZIQ AZREL BIN HAIRUL AZWAN; PROF. Ts. Dr. ANGZZAS SARI BINTI MOHD KASSIM (Progress in Engineering Application and Technology, 2026)
With the rising incidence of hair loss and scalp disorders, there is an increasing demand for hair care products that are safe, effective, and environmentally sustainable. Most commercial hair serums currently available contain synthetic chemical components, which may cause scalp irritation, long-term damage, and potential safety concerns for consumers. In contrast, this study aimed to develop a microsized natural hair growth and scalp oil serum formulated with Curcuma Xanthorizza, Curcuma longa, and Zingiber officinale, plant materials well recognised for their antioxidant and anti-inflammatory properties, which are essential for maintaining scalp health and supporting hair follicle function. Subcritical water extraction was employed to obtain bioactive-rich extracts while preserving compound stability and minimising the use of organic solvents. Formulation optimisation was performed using Design of Experiments (DoE) methodology, followed by ultrasonication to achieve microscale particle size, thereby enhancing dispersion stability and follicular targeting. Comprehensive physicochemical characterisation was conducted, including pH, viscosity, and particle size analysis, alongside functional evaluations such as antioxidant activity using DPPH and FRAP assays, and anti-inflammatory activity assessed via the bovine serum albumin (BSA) protein denaturation method. The results demonstrated that the formulated microsized serum exhibited a suitable pH range (4.5 5.0) for scalp application, a stable microscale particle size distribution (365–567 nm), and significant antioxidant activity (89–98% inhibition), together with notable anti-inflammatory activity (96–98.4%), when compared with the corresponding raw herbal extracts. The microsized delivery system enhanced bioactive retention and promoted localised activity at the scalp and hair follicle regions. Overall, this study confirms the feasibility of integrating microtechnology with herbal bioactives to develop a safe, effective, and eco-friendly hair growth and scalp serum. These findings provide valuable insights into natural cosmeceutical formulation and support the potential application of microsized delivery systems in the development of advanced hair care products.